THE USE OF DIGITAL TOOLS IN THE MANAGEMENT OF MIGRATION PROCESSES - Gulmurodov Kamoliddin Abduqodir ugli (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the development of the Uzbek economy, labor migration, causes, consequences, problems of labor migration, employment problems, negative and positive aspects of migration, the most important economic and social causes of unemployment, ie unemployment, Finding suitable jobs, obtaining higher and secondary special education, ie studying and other types of problems are studied and scientifically based proposals are given to solve the problems.